Faith Ringgold narrating the world in pattern and colour - Jackson, Sharna (Dorling Kindersley Limited, 2021)
See the world through Faith Ringgold's eyes and be inspired to produce your own masterpieces. Have you ever wondered exactly what your favourite artists were looking at to make them sculpt, sew, or paint the way they did? In this book, created in collaboration with The Metropolitan Museum of Art, meet inspiring American artist and activist Faith Ringgold. Step into her life and learn what led her to mix different media and craft powerful stories into quilts. Travel with her to the places that influenced her and see the causes she fought for
"The MET" -- Cover
Keywords: Ringgold, Faith -- 1930-2024; Malerin; Künstlerin; Schwarze; USA; Ringgold, Faith / Juvenile literature; Women artists / Juvenile literature; African American women artists / Juvenile literature; Mixed media (Art) / Juvenile literature; Quilts / Juvenile literature; Civil rights workers / Juvenile literature; Biografie; Sachbilderbuch